A NOTE ON THE EXISTENCE OF A UNIVERSAL POLYTOPE AMONG REGULAR 4-POLYTOPES - Jin Akiyama; Sin Hitotumatu; Ikuro Sato (Journal of the Indonesian Mathematical Society, 2013)
pdf abstractDOI : http://dx.doi.org/10.22342/jims.19.1.128.41-47